2018
DOI: 10.3748/wjg.v24.i1.35
|View full text |Cite
|
Sign up to set email alerts
|

Emodin and baicalein inhibit sodium taurocholate-induced vacuole formation in pancreatic acinar cells

Abstract: AIMTo investigate the effects of combined use of emodin and baicalein (CEB) at the cellular and organism levels in severe acute pancreatitis (SAP) and explore the underlying mechanism.METHODSSAP was induced by retrograde infusion of 5% sodium taurocholate into the pancreatic duct in 48 male SD rats. Pancreatic histopathology score, serum amylase activity, and levels of tumour necrosis factor alpha (TNF-α), interleukin 6 (IL-6), and IL-10 were determined to assess the effects of CEB at 12 h after the surgery. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…9,10 To elucidate their therapeutic roles in the treatment of SAP, the ingredients of the herbs have been extensively assessed via in silico, in vitro, and in vivo experiments. Emodin, as a predominant compound of rhubarb, has been reported to inhibit vacuole formation in the acinar cells, 11 attenuate autophagy response, 12 and protect against the oxidative stress and inflammasome signals in SAP. 13,14 However, the role of emodin in the intestinal barrier injury and immune response caused by SAP is still limited.…”
mentioning
confidence: 99%
“…9,10 To elucidate their therapeutic roles in the treatment of SAP, the ingredients of the herbs have been extensively assessed via in silico, in vitro, and in vivo experiments. Emodin, as a predominant compound of rhubarb, has been reported to inhibit vacuole formation in the acinar cells, 11 attenuate autophagy response, 12 and protect against the oxidative stress and inflammasome signals in SAP. 13,14 However, the role of emodin in the intestinal barrier injury and immune response caused by SAP is still limited.…”
mentioning
confidence: 99%
“…Out of the active compounds of CQCQD, baicalein, baicalin, chrysin, honokiol, magnolol, and salidroside, all demonstrated marked potential for high affinity binding to AKT1, with chrysin being the most potent. While previous studies have reported that some of these compounds can improve AP in the in vivo or in vitro models ( Li et al, 2018 ; Pu et al, 2019 ), the evidence that CQCQD components modulate oxidative stress or the PI3K/Akt pathway is marginal. In different diseases, honokiol was used as an inhibitor of Akt activation ( Zhai et al, 2005 ), and chrysin was postulated to modulate the PI3K/Akt pathway ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…As anti-inflammatory mediators, IL-4 and IL-10 have been suggested to be valuable treatment strategies for SAP. 38,39 However, the expression of IL-4 and IL-10 was down-regulated in the serum and spleen of SAP rats, but this pattern could be inverted by splenectomy. In addition, the 13 differentially expressed cytokines were significantly enriched in the GO terms inflammatory response, positive regulation of major histocompatibility complex class II biosynthetic process, positive regulation of B-cell proliferation and immune response, and the KEGG pathways cytokine-cytokine receptor interaction, TNF signaling, and JAK-STAT signaling.…”
Section: Discussionmentioning
confidence: 97%